An Ethno-Pharmaco-Botanical Review of Hamsapadi –Adiantum lunulatum Burm. F. (A. Philippense Linn.) - G, Pallavi. (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACT Hamsapadi, Adiantum lunulatum Burm.f. (A. Philippense Linn) usually known as ‘Walking Maiden hair fern’ is used as an ornamental plant and widely distributed in India. It is commonly found in wet, shaded areas and on moist mud walls during monsoon. It is a drug with a significant ethno- botanical & therapeutic importance. It was in use since time immemorial for medicinal and other uses. Several phyto-constituents have been isolated and identified from different parts of the plant such as Carotenoids, Flavonoids, Nortriterpene-adiantone etc. The dried whole plant has been used as a medicine for bronchitis and cough. It is used in bleeding diseases, burning sensation, erysipelas, epileptic fits, dysentery, strangury and elephantiasis. Few studies have been undertaken till date to substantiate its pharmacological activities such as antibacterial, antifungal, antioxidant, hypotensive etc. This article reviews the complete details of the drug such as Morphology, Distribution, Ethno botanical claims, and Pharmacological activities.